Simultaneous determination of niacin and pyridoxine at trace levels by using diode array high-performance liquid chromatography and liquid chromatography with quadrupole time-of-flight tandem mass spectrometry - Sel, Sabriye; Er, Elif Ozturk; Bakirdere, Sezgin (WILEY-V C H VERLAG GMBH, 2017)
A highly sensitive and simple diode-array high-performance liquid chromatography and liquid chromatography with quadrupole time-of-flight tandem mass spectrometry method was developed for the simultaneous determination of niacin and pyridoxine in pharmaceutical drugs, tap water, and wastewater samples. To determine the in vivo behavior of niacin and pyridoxine, analytes were subjected to simulated gastric conditions. The calibration plots of the diode-array high-performance liquid chromatography and liquid chromatography with quadrupole time-of-flight tandem mass spectrometry method showed good linearity over a wide concentration range with close to 1.0 correlation coefficients for both analytes. The limit of detection/limit of quantitation values for liquid chromatography quadrupole time-of-flight tandem mass spectrometry analysis were 1.98/6.59 and 1.3/4.4 mu g/L for niacin and pyridoxine, respectively, while limit of detection/limit of quantitation values for niacin and pyridoxine in high-performance liquid chromatography analysis were 3.7/12.3 and 5.7/18.9 mu g/L, respectively. Recovery studies were also performed to show the applicability of the developed methods, and percentage recovery values were found to be 90-105% in tap water and 94-97% in wastewater for both analytes. The method was also successfully applied for the qualitative and quantitative determination of niacin and pyridoxine in drug samples.
Keywords: gastric conditions; niacin; pyridoxine; waste water; WATER-SOLUBLE VITAMINS; PHARMACEUTICAL-PREPARATIONS; RIBOFLAVIN; THIAMINE; PLASMA; FOOD; TAURINE; TABLETS; ACID; Chemistry